Bangladesh : Can Incentives for Community Authors Reduce Shortages in Minority Language Reading Materials? - World Bank (World Bank, Washington, DC, 2020)
Bangladesh has one of the world’s largest school systems with more than 21 million students enrolled in pre-primary and primary education. However, only 58 percent of 10-year-olds in Bangladesh are able to read a simple passage with little or no help, a smaller proportion than other countries including Botswana, Cambodia, or India. One of the challenges faced is the country’s wide variety of languages, 41 in total, of which 16 are in common use. In Bangladesh, indigenous students, those from outside the main Bengali ethnic group are half as likely to complete primary school. One of the reasons for that is that they do not understand the national language, Bangla, which is the language used in their schools. Evidence from a wide range of countries suggests that allowing students to learn in their mother tongue, at least in the early years of education, improves learning outcomes.